Analyst Motivation - Factor of Effective Team Communications Between Fmwarder and Principal - Dorotea Žic (Promet - Traffic&Transportation, 1970)
Analyst motivation is to develop team work with forwarderand his principal in order to realise effective communicationbetween forwarder and principal, according to the set problemsand limitations directed by the surroundings in the system of internationalforwarding agency, foreign trade, traffic and informationsyscems.The analyst cares for personal and collective motivationdevelopment, creating convenient conditions of team work offorwarder and his principal in order to model the process anddata in the most creative way using the Stntctured SystemsAnalysis method. By applying this method, the analyst createscomplete documentation of the process model: Functional DecompositionDiagram, Context Diagram, Data Flow Diagramof other levels of abstraction, logic process definition, and descriptionof data flow structure and description of data bufferstntcture.The team tries to achieve the optimal diversity with definitegoodwill of analyst, forwarder and principal, and diverse characteristicsof personality, professional knowledge and balanceof all members.